Reducing poverty in Latin America and the Caribbean - Galiani, Sebastian ([s.n.] [S.l.], 2007)
Looks at poverty in Latin America and the Caribbean and posits that economic growth is a powerful instrument in reducing absolute poverty. Presents a set of redistributive interventions that have proven to be cost-effective in reducing poverty and inequality in LAC.